Stigma and GPs' perceptions of dementia. (2nd April 2016) - Gove, D.; Downs, M.; Vernooij-Dassen, M.; Small, N.
Abstract : Objectives: General practitioners (GPs) are crucial to improving timely diagnosis, but little is reported about how they perceive dementia, and whether their perceptions display any elements of stigma. The aim of this study was to explore how GPs' perceptions of dementia map onto current conceptualizations of stigma and whether GPs feel that stigma affects timely diagnosis. Methods: Twenty-three GPs from England were interviewed by telephone. Data were analyzed by means of content analysis. This involved open coding followed by the application of a coding framework derived from the literature to explore how and to what extent their perceptions relate to stigma as well as the unique nature of their perceptions. Results: Three themes emerged from the analysis: (1) 'making sense of dementia', (2) 'relating perceptions of dementia to oneself' and (3) 'considering the consequences of dementia'. GPs' perceptions of dementia mapped onto current conceptualizations of stigma. Perceptions about dementia that were linked to their own existential anxiety and to a perceived similarity between people with dementia and themselves were particularly salient. GPs perceived dementia as a stigma which was gradually being overcome but that stigma still hindered timely diagnosis. They provided examples of structural discrimination within the health service, including lack of time for patients and shortcomings in training that were to the detriment of people with dementia. Conclusion: Measures to involve GPs in tackling stigma should include training and opportunities to explore how they perceive dementia, as well as support to address structural discrimination.